Evidence Review for Teacher Praise to Improve Students' Classroom Behavior. (January 2019) - Moore, Tara C.; Maggin, Daniel M.; Thompson, Kelly M.; Gordon, Jason R.; Daniels, Stephanie; Lang, Lucinda E.
In this study, a systematic review was conducted to examine the evidence base for teacher praise for students without severe disabilities in K–12 classroom settings. Specifically, reviewers followed standards presented by the Council for Exceptional Children and the What Works Clearinghouse to evaluate the methodological quality of 30 studies meeting inclusion criteria. Only 11 studies were rated as being methodologically sound. The review team then classified effects of the 11 methodologically sound studies and provided an overall evidence-based classification for the practice using both sets of standards. Results indicated there is currently insufficient evidence to identify teacher praise as an evidence-based practice for this population of students. A further evaluation of this research base provided no discernable patterns for when and for whom teacher praise is likely to be effective. Implications for practice and future research are provided.